If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9=-2(a+4)9a
We move all terms to the left:
9-(-2(a+4)9a)=0
We calculate terms in parentheses: -(-2(a+4)9a), so:We get rid of parentheses
-2(a+4)9a
We multiply parentheses
-18a^2-72a
Back to the equation:
-(-18a^2-72a)
18a^2+72a+9=0
a = 18; b = 72; c = +9;
Δ = b2-4ac
Δ = 722-4·18·9
Δ = 4536
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$a_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$a_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{4536}=\sqrt{324*14}=\sqrt{324}*\sqrt{14}=18\sqrt{14}$$a_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(72)-18\sqrt{14}}{2*18}=\frac{-72-18\sqrt{14}}{36} $$a_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(72)+18\sqrt{14}}{2*18}=\frac{-72+18\sqrt{14}}{36} $
| 8x-21=-5 | | 215=q-396 | | 4x-10=5x-22=3x+2 | | 5x+2(7−x)=23 | | 6t+3-2=6 | | -26=-8y+6(y-2) | | 4(y+3)+2y=7 | | 12y=1.2 | | 68=3x+17 | | 3y=-4+2 | | -1=-7y+5(y+3) | | 3z-1/3-4=4z+1/4-5z | | 12=t-47 | | 8x+64=-9 | | -72=w+-5 | | x+3-(2x-4)=4+2(3x-1) | | (-10)(5x)(-8)=x | | 6x=7=8x-13 | | 43=3c-5 | | -6+c=38 | | (X+3)^2=x^2+3^2 | | 4=-7+m | | 2x+5=8x+11 | | -30-n=12 | | X-(4x-8)=5x-(x+21) | | 2x+2(2x-2)=68 | | 80=4v+12 | | 6g-10=2(3g-5) | | 1^2-1=(1+1)(x-1) | | 1/3(3t+6)+1=5 | | -2(x+6)-6x=4(x-3) | | 3(2+x)=x+16 |